Nuclear medicine in clinical diagnosis and treatment - Murray, I. Provan C; Ell, Peter Josef; Strauss, H. William (Churchill Livingstone, 1994)
A two-volume textbook of nuclear medicine with an emphasis on practical applications. This problem-based approach should make the book a useful guide to the overall management of patients and therefore valuable for the clinician as well as the radiologist. The book is organized on the basis of clinical problems and the contribution which nuclear medicine can make to solve these problems. The extensive range of illustrations make the book a practical guide to interpretation, with figures, demonstrating normal and abnormal images, with examples of rare conditions. Whilst the book confines technical details to particular sections and appendices, it nonetheless provides a full clinical commentary which is amplified by the illustrations. It also features descriptions of unexpected findings with statistics of incidence and helpful references. A comprehensive account of the subject is presented here in a form that is meaningful and appropriate to clinicians, to assist decision-making on treatment options and prognosis by an international mix of contributors.
Keywords: radiologie, nukleární medicína a zobrazovací metody